Respiratory viral infections awaken metastatic breast cancer cells in lungs - Shi B. Chia; Bryan J. Johnson; Junxiao Hu; Felipe Valença-Pereira; Marc Chadeau-Hyam; Fernando Guntoro; Hugh Montgomery; Meher P. Boorgula; Varsha Sreekanth; Andrew Goodspeed; Bennett Davenport; Marco De Dominici; et al. (Nature, 2025)
Abstract Breast cancer is the second most common cancer globally, with most deaths caused by metastatic disease, often following long periods of clinical dormancy 1 . Understanding the mechanisms that disrupt the quiescence of dormant disseminated cancer cells (DCCs) is crucial for addressing metastatic progression. Infections caused by respiratory viruses such as influenza and SARS-CoV-2 trigger both local and systemic inflammation 2,3 . Here we demonstrate, in mice, that influenza and SARS-CoV-2 infections lead to loss of the pro-dormancy phenotype in breast DCCs in the lung, causing DCC proliferation within days of infection and a massive expansion of carcinoma cells into metastatic lesions within two weeks. These phenotypic transitions and expansions are interleukin-6 dependent. We show that DCCs impair lung T cell activation and that CD4 + T cells sustain the pulmonary metastatic burden after the influenza infection by inhibiting CD8 + T cell activation and cytotoxicity. Crucially, these experimental findings align with human observational data. Analyses of cancer survivors from the UK Biobank (all cancers) and Flatiron Health (breast cancer) databases reveal that SARS-CoV-2 infection substantially increases the risk of cancer-related mortality and lung metastasis compared with uninfected cancer survivors. These discoveries underscore the huge impact of respiratory viral infections on metastatic cancer resurgence, offering new insights into the connection between infectious diseases and cancer metastasis.